Molecular tools for epidemiological investigations into Legionella pneumophila environmental diffusion: applications for the prevention (Italian Journal of Public Health, 2004)
Microbiological typing is a useful tool in the epidemiological investigations of infectious diseases, given that it allows for the identification of specific clones among a set of isolates. In the last ten years several studies have demonstrated how genotyping methods can be useful in Legionella spp investigations in hospital setting (e.g., epidemic events). Pulsed field gel electrophoresis and amplified fragment length polymorphisms are the current typing methods of choice, even though multilocus sequence typing will probably be the gold standard of the future.